2016
DOI: 10.3847/0004-6256/152/6/169
|View full text |Cite
|
Sign up to set email alerts
|

2014–2015 Multiple Outbursts of 15p/Finlay

Abstract: -3 -Multiple outbursts of a Jupiter-family comet, 15P/Finlay, occurred from late 2014 to early 2015. We conducted an observation of the comet after the first outburst and subsequently witnessed another outburst on 2015 January 15.6-15.7. The gas, consisting mostly of C 2 and CN, and dust particles expanded at speeds of 1,110 ± 180 m s −1 and 570 ± 40 m s −1 at a heliocentric distance of 1.0 AU. We estimated the maximum ratio of solar radiation pressure with respect to the solar gravity β max = 1.6 ± 0.2, which… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 52 publications
2
25
0
Order By: Relevance
“…If 72P/D-F indeed had dormant periods in the past, the dust spatial density or the volume filled by the trail, or both, may be overestimated by the IMEX model. In a similar way, comet 15P/Finlay may also be evolving into a transitional asteroid-like object (Beech et al 1999), although it possess the ability for repetitive energetic outbursts (Ishiguro et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…If 72P/D-F indeed had dormant periods in the past, the dust spatial density or the volume filled by the trail, or both, may be overestimated by the IMEX model. In a similar way, comet 15P/Finlay may also be evolving into a transitional asteroid-like object (Beech et al 1999), although it possess the ability for repetitive energetic outbursts (Ishiguro et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…q = 1.7, Kleyna et al 2019) and larger indices (e.g. q = 3.8, Ishiguro et al 2016b) have been reported. If the particle radius range extends from minimum a min to maximum a max , the average radius in a q = 3.5 distribution is a = (a min a max ) 1/2 .…”
Section: Observationsmentioning
confidence: 94%
“…The kinetic energy per unit mass has been used as metric to test the origins of cometary outbursts. Ishiguro et al (2016) found that the kinetic energy per unit mass for outbursts of 15P/Finlay, 17P/Holmes, and 332P/Ikeya-Murakami are ∼ 10 4 J kg −1 , suggesting similar causes. Thus, studying the energetics and/or dust-to-gas ratio of the 46P outbursts may help discern the driving mechanisms.…”
Section: Mini-outbursts Of Wirtanen and Other Cometsmentioning
confidence: 97%
“…Outbursts are common events with a wide range of strengths (Ishiguro et al 2016). Discoveries of outbursts are becoming more prevalent in recent years due to our increased ability to monitor comets (both in the professional and amateur communities), and with the increased efficiencies of survey telescopes and precise all-sky photometric catalogs (e.g., PS1 and SkyMapper; Tonry et al 2018b;Wolf et al 2018).…”
Section: Potential For Future Mini-outburst Studiesmentioning
confidence: 99%